2012
DOI: 10.1055/s-0031-1297247
|View full text |Cite
|
Sign up to set email alerts
|

Did Survival Improve after the Implementation of Intraoperative Neuronavigation and 3D Ultrasound in Glioblastoma Surgery? A Retrospective Analysis of 192 Primary Operations

Abstract: Our study demonstrates that survival has improved within the same period that intraoperative ultrasound and neuronavigation was introduced and established in our department. The demonstrated association is a necessity for causation, but given the nature of this study, one must be cautious to claim causality. The improvement was, however, significant after adjustment for known major prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…A more practical and cost-efficient tool for planning and guiding surgeries is intraoperative US (7,(12)(13)(14)(15). It enables acquisition of real-time information during and after tumor resection but suffers from several artifacts and lack of training by most neurosurgeons.…”
Section: Preoperative Mr Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…A more practical and cost-efficient tool for planning and guiding surgeries is intraoperative US (7,(12)(13)(14)(15). It enables acquisition of real-time information during and after tumor resection but suffers from several artifacts and lack of training by most neurosurgeons.…”
Section: Preoperative Mr Imagingmentioning
confidence: 99%
“…It enables acquisition of real-time information during and after tumor resection but suffers from several artifacts and lack of training by most neurosurgeons. However, when coupled with navigation systems, orientation is improved and the brain shift can be compensated for, with improved orientation and image interpretation (7,(12)(13)(14)(15)(16). Some investigators have shown that US applied to neuronavigation systems improves patient survival in the resection of GBM (13,17).…”
Section: Preoperative Mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the most durable long-term survival benefit for patients with gliomas, complete eradication of tumors while sparing the normal brain parenchyma remains the most challenging task for neurosurgeons (3,6,14,15). Because of this daunting task in patients with gliomas, numerous intraoperative imaging-guided surgical techniques have been developed in an effort to extend survival and improve quality of life (5,6,12,25,26). Use of a single imaging modality to guide surgery has inherent limitations and disadvantages.…”
Section: Experimental Studies: Motexafin Gadolinium-enhanced Moleculamentioning
confidence: 99%
“…Further, as rightly pointed out by Barbosa et al, cost-effectiveness studies are crucial especially when the other objective benefits are limited. In this context, it may be appropriate to note that intraoperative ultrasound has emerged as a potentially useful cost-effective alternative to IOMR [6,5]. Further well-designed, prospective studies evaluating IOUS as well as comparing IOMR and IOUS are warranted.…”
mentioning
confidence: 99%